Microstructure, residual stress, and mechanical properties evolution of a Cu–Fe–P alloy under different conditions - Jingzhao Yang; Kun Bu; Yanjun Zhou; Kexing Song; Tao Huang; Xiaowen Peng; Haitao Liu; Yibo Du (Journal of Materials Research and Technology, 2023)
The evolution of the mechanical characteristics, residual stresses, and microstructure of a Cu–Fe–P alloy during machining was investigated, and the influence mechanism of the microstructure on the residual stress and strength of the Cu–Fe–P alloy was confirmed. The findings suggest that the tensile strength, transverse direction (TD), and rolling direction (RD) residual stresses in the cold-rolled state are 516 MPa, −80 MPa and −36 MPa, respectively, which are 76.1%, 93.8%, and 72.2% higher than those in the hot-rolled state, respectively. In addition, after annealing at high temperatures, the tensile strength, TD, and RD residual stresses of the Cu–Fe–P alloy decreased to 344 MPa, −9 MPa and −24 MPa, respectively, which were 33.3%, 88.8%, and 33.3% smaller than those of the cold-rolled alloy, respectively. The strength and residual stress of the Cu–Fe–P alloy are intriguing. The primary influencing aspects of the strength and residual stress are dislocations, grain boundaries, and textures. The residual stress of the Cu–Fe–P alloy may be controlled while maintaining strength by appropriately increasing the proportion of recrystallized grains and decreasing the dislocation density and volume fraction of the Brass texture, respectively. These outcomes serve as a guide for improving the service performance of Cu–Fe–P alloys.